Ambient factors, design factors, and social factors towards satisfaction by irritation as mediating variabel - Cyntiara Wiranisa; Astri Yuza Sari (Marketing Management Studies, 2021)
This study aims to analyze the influence of Ambient Factors, Design Factors, and Social Factors on Satisfaction with Irritation as a Mediation Variable for Foodmart Basko Grand Mall Visitors Padang. This research is a causative descriptive research. The population of this research is 230 respondents who visited Foodmart Basko Grand Mall Padang. While the number of research samples is determined based on a non-probability method with a purposive sampling technique. The analytical method used is descriptive analysis. This research was analyzed using SPSS v21 software. The results of this study indicate that: The ambient factor variable has a positive and significant effect on irritation, the design factor variable has a positive and significant effect on irritation, social factors have no effect on irritation, the irritation variable has a positive effect on satisfaction, the irritation variable is not able to mediate ambient factors on satisfaction, the irritation variable is able to mediate design factors on satisfaction, factor variables have an effect on satisfaction which is mediated by irritation